Validated Stability-Indicating Assay Method for Simultaneous Determination of Aceclofenac and Thiocolchicoside using RP-HPLC - Samanthula, G.; Shrigod, V. V.; Patel, P. N. (Drug Research, 2014)
A rapid, accurate, precise, robust and specific stability indicating RP-HPLC method has been developed and validated for simultaneous determination of fixed dose combination of Aceclofenac (ACF) and Thiocolchicoside (THC). Combinations and marketed tablets were subjected to stress conditions such as oxidation, hydrolysis, photolysis and heat. Successful separation of drugs from stress degradation products was achieved on Kromasil C18 (250×4.6 mm, 5 μm) column at 30°C using gradient mobile phase system consisting of (A) 10 mM ammonium acetate pH 5.00 buffer and (B) acetonitrile: water (70:30 v/v). The flow rate was 1.0 mL/min with UV detection at 265 nm. The retention time of THC and ACF was 13.29 and 22.20 min respectively. Peak purity of both the drugs was passing in all degradation conditions demonstrates the specificity of assay method for their estimation in presence of degradation products. The developed HPLC method was validated for linearity, accuracy, precision and robustness. The linearity of the proposed method was investigated in the range of 80–280 µg/mL for ACF and 6.4–22.4 µg/mL for THC. The utility of the procedure was verified by its application to marketed formulations.
Keywords: Thiocolchicoside; Aceclofenac; stability-indicating assay method; RP-HPLC